New species and records of Neopronematus (Acari: Iolinidae) from Iran with a key to world species - Darbemamieh, Maryam; Hajiqanbar, Hamidreza; Khanjani, Mohammad; Kaźmierski, Andrzej (Zootaxa, 2015)
In this paper, Neopronematus kamalii Darbemamieh and Hajiqanbar sp. nov. (Acari: Prostigmata: Iolinidae), collected from apricot leaves in Kermanshah province, Iran, is described and illustrated. Also, the following species were collected and identified from Kermanshah province, Iran: Neopronematus rapidus (Kuznetzov, 1972), Neopronematus solani Łaniecka and Kaźmierski, 2013; Neopronematus sepasgosariani Sadeghi, Łaniecka and Kaźmierski, 2012; Neopronematus lundqvisti Sadeghi, Łaniecka and Kaźmierski, 2012; and Neopronematus neglectus (Kuznetzov, 1972). Some information about the genus, morphologically close species, remarks and a key to Neopronematus species of the world are given as well.